Pre-clinical Research on Bladder Toxicity After Radiotherapy for Pelvic Cancers: State-of-the Art and Challenges - Zuppone, Stefania; Bresolin, Andrea; Spinelli, Antonello E.; Fallara, Giuseppe; Lucianò, Roberta; Scarfò, Federico; Benigni, Fabio; Di Muzio, Nadia; Fiorino, Claudio; Briganti, Alberto; Salonia, Andrea; Montorsi, Francesco; et al. (Frontiers in Oncology, 2020)
Despite the dramatic advancements in pelvic radiotherapy, urinary toxicity remains a significant side-effect. The assessment of clinico-dosimetric predictors of radiation cystitis (RC) based on clinical data has improved substantially over the last decade; however, a thorough understanding of the physiopathogenetic mechanisms underlying the onset of RC, with its variegated acute and late urinary symptoms, is still largely lacking, and data from pre-clinical research is still limited. The aim of this review is to provide an overview of the main open issues and, ideally, to help investigators in orienting future research. First, anatomy and physiology of bladder, as well as the current knowledge of dose and dose-volume effects in humans, are briefly summarized. Subsequently, pre-clinical radiobiology aspects of RC are discussed. The findings suggest that pre-clinical research on RC in animal models is a lively field of research with growing interest in the development of new radioprotective agents. The availability of new high precision micro-irradiators and the rapid advances in small animal imaging might lead to big improvement into this field. In particular, studies focusing on the definition of dose and fractionation are warranted, especially considering the growing interest in hypo-fractionation and ablative therapies for prostate cancer treatment. Moreover, improvement in radiotherapy plans optimization by selectively reducing radiation dose to more radiosensitive substructures close to the bladder would be of paramount importance. Finally, thanks to new pre-clinical imaging platforms, reliable and reproducible methods to assess the severity of RC in animal models are expected to be developed.